Ishlah dan Wasathah dalam Penyelesaian Sengketa Waris: Studi Kasus di Desa Waibau, Kecamatan Sanana - Erina Junaidi; Muhamad Ibnal Trian Has Duwila (Sekolah Tinggi Agama Islam Babussalam Sula, 2026)
Inheritance disputes among rural Muslim families are often triggered by one party's unilateral control over productive assets, such as land, houses, or plantations, before a division is agreed upon. Prior studies extensively examine dispute resolution through Religious Courts or formal sub-district mediation, yet empirical accounts of family deliberation and village mediation in archipelagic regions such as the Sula Islands remain scarce. This study describes the forms of inheritance dispute resolution in Waibau Village, Sanana, and examines them from an Islamic legal perspective. Using a qualitative descriptive case study approach, data were collected through in-depth interviews with the village head, a religious leader, and disputing parties, supported by observation and documentation. Findings reveal a tiered pattern: family deliberation first, mediation by the village head and religious leader when deliberation stalls, and litigation as a strongly avoided last resort. From an Islamic legal standpoint, this pattern reflects ishlah and wasathah, prioritizing hifzh al-nasl over hifzh al-mal. This study contributes an empirical account of inheritance law values practiced in a coastal village community